On some solutions of topical problems of public purchasing auctions in Russia - D. S. Khvalynskiy (Russian Journal of Economics and Law)
Objective: to elaborate methods of increasing efficiency and results of public purchases in Russian public auctions. Methods: systemic analysis, statistical and abstract-logical methods. Results: Basing on the estimation of situation in the sphere of public purchases, made by the results of electronic auctions in the Russian Federation, it is proved that the current form of the reverse English auction is inefficient. The necessity is grounded to elaborate new designs of the auctions. Scientific novelty: Formed the list of the main reasons of inefficiency of public purchasing auctions in Russia; grounded the necessity to use other forms of auctions; made proposals to use Dutch auctions and sealed stakes auctions; conditions of their application are discussed. Practical value: Possibility to optimize the state management expenditures in Russia, to increase the quality of production purchased for state and municipal needs.